2012
DOI: 10.1136/annrheumdis-2012-202220
|View full text |Cite
|
Sign up to set email alerts
|

The immunogenicity of anti-TNF therapy in immune-mediated inflammatory diseases: a systematic review of the literature with a meta-analysis

Abstract: ADA reduces drug response, an effect that can be attenuated by concomitant immunosuppression, which reduces ADA frequency. Drug immunogenicity should be considered for the management of patients receiving biological therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
235
1
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(269 citation statements)
references
References 60 publications
15
235
1
13
Order By: Relevance
“…In a metaanalysis that evaluated the presence and effects of anti-drug antibodies in patients with different inflammatory diseases, such as rheumatoid arthritis, spondyloarthropathies and inflammatory bowel diseases, the drug response was reduced if anti-drug antibodies could be detected in the sera of patients. Among different diseases the effect of anti-drug antibody positivity on TNFi responses was more pronounced in AS and spondyloarthropathies than in other diseases (27). As concomittant treatment with methotrexate or other immunosuppressive drugs reduces the production of these antibodies, and as in axial form of spondyloarthropathies these type of drugs are usually not administered, it may highlight the necessity of determination of anti-drug antibodies in cases of loss of efficacy in AS, which may give further support for the decision of switching.…”
Section: Discussionmentioning
confidence: 93%
“…In a metaanalysis that evaluated the presence and effects of anti-drug antibodies in patients with different inflammatory diseases, such as rheumatoid arthritis, spondyloarthropathies and inflammatory bowel diseases, the drug response was reduced if anti-drug antibodies could be detected in the sera of patients. Among different diseases the effect of anti-drug antibody positivity on TNFi responses was more pronounced in AS and spondyloarthropathies than in other diseases (27). As concomittant treatment with methotrexate or other immunosuppressive drugs reduces the production of these antibodies, and as in axial form of spondyloarthropathies these type of drugs are usually not administered, it may highlight the necessity of determination of anti-drug antibodies in cases of loss of efficacy in AS, which may give further support for the decision of switching.…”
Section: Discussionmentioning
confidence: 93%
“…Numerous literature reports have stated that immunogenicity negatively impacted the therapeutic outcomes of biological treatments, such as immunogenicity-associated secondary treatment failure (5,7,8) for monoclonal antibodies and recombinant proteins. A reduction in the systemic exposure can be associated with the observed immunogenicity and a potential explanation for the reduced efficacy to biologics.…”
Section: Introductionmentioning
confidence: 99%
“…12 In Garces et al research, ETN effects were found less atherogenic than infliximab which supports our findings in this case. 13 They showed a prominent increase in HDL after 1 year of ETN treatment and showed no change in cholesterol and LDL levels. Our case also showed an improvement in HDL-C levels under ETN treatment.…”
Section: Discussionmentioning
confidence: 92%